Ideational Meaning and Visual Aspect Relations in Virginia Allum’s Videos to Teach English for Nursing - Sherly Arwinda Arwinda; Sri Wuli Fitriati; Djoko Sutopo (English Education Journal, 2023)
English for Nursing (ENP) focuses on developing the need for English, which can support medical personnel's work and fulfill professional assessment needs. Learning English from many media, one of them through video, can give nursing students experience about their work in the real world by studying what the video presents. This recent study aims to explain the realization of ideational meaning and its relations to visual aspect as the semiotic systems in English for Nurses Videos. This study was a qualitative study that used discourse analysis. The data were taken from conversation text and captured images on the three videos on Virginia Allum’s YouTube channel. This study implemented multimodal analysis to observe the ideational meaning as the linguistic and visual aspects of the videos. The ideational meaning was analyzed using SFL to later look for its relationship with the visual aspect. This study found that ideational meaning and visual aspects are related to their video presentation. The type of process is dominated by 77 relational processes, 37 actors, and 11 manner as the circumstance. Visual aspects indicate the characteristics following the themes surrounding the hospital, health, and the identity of the nursing profession itself. Ideas and visuals support each other because they simultaneously provide experience to the viewer through the video being watched without the viewer doing the action themselves. This study suggested that lecturers and students can consider this study’s result to improve the use of videos as multimodal text to support teaching learning activities in English for Nursing.